Coronal Fractures of the Scaphoid: A Review - Slutsky, David J.; Herzberg, Guillaume; Shin, Alexander Y.; Buijze, Geert A.; Ring, David C.; Mudgal, Chaitanya S.; Leung, Yuen-Fai; Dumontier, Christian (Journal of Wrist Surgery, 2016)
Coronal (or frontal plane) fractures of the scaphoid are distinctly uncommon. There are few published reports of coronal fractures of the scaphoid. This fracture is often missed on the initial X-ray films. A high index of suspicion should exist when there is a double contour of the proximal scaphoid pole on the anteroposterior X-ray view. A computed tomography scan is integral in making the diagnosis. Early recognition is key in salvaging the scaphoid fracture and in preventing articular damage. Level of Evidence IV. Retrospective case series.
Keywords: scaphoid; fracture; coronal